Filozofia społeczna Leszka Nowaka w perspektywie teoretycznej i systematycznej - Waldemar Czajkowski, Waldemar Czajkowski (Człowiek i Społeczeństwo, 2016)
The paper presents two complementary views on the social philosophy of Leszek Nowak – one of the most prominent, original and versatile Polish philosophers: historical and systematic. As regards the historical perspective, some brief remarks on the history of Polish analytical philosophy have been made. Two points have been underscored: First, the continuity of this history – from its creator Kazimierz Twardowski to Leszek Nowak, and his disciples. And second: the plurality of philosophical worldviews (Christian, liberal, Marxist...) which were analytically elaborated by Polish philosophers. As regards the systematic perspective, two elements are to be mentioned. Firstly, a number of arguments have been formulated to support author’s conviction that non-Marxian historical materialism is one of the most important social philosophies. Secondly, some critical remarks on this philosophy have been made.